Norm Entrepreneurs in Human Rights Campaign: The Study of KontraS and Imparsial - Muh Afit Khomsani; Ani Widyani Soetjipto (Jurnal Ilmiah Hubungan Internasional, 2022)
Civil society organisations or CSOs are unique compared to other groups. They help advocate the society by mentoring, raising public awareness, and campaigning values to improve the quality of understanding the public issues. By analyzing the rejection of the death penalty, this study examines the role of KontraS and Imparsial as norm entrepreneurs in human rights campaigns. Both view the death penalty as incompatible with the universal human rights norm, and the government should comprehensively pay greater attention to this issue. With this belief as a rationale, KontraS and Imparsial are motivated to promote the rejection of the penalty as depicted in their campaigns. The two organizations conduct malicious actions like criticism, demonstration, and collaborative strategies such as research, education, and community empowerment in human rights campaigns. This paper is qualitative research using an intensive literature review combined with in-depth interviews. The findings revealed that both succeeded in overspreading counter norms to create political debates regarding death punishment. However, due to the coalition’s socio-political dynamics and internal factors, KontraS and Imparsial failed to influence the actors and state policies to abolish the capital penalty.